KINEMATIC MOTION OF POSITIVE CARBON ION SPECIES: A PROPOSAL METHOD - M.S. Roslana; Saktioto '; J. Ali (Komunikasi Fisika Indonesia, 2014)
The ion carbon species are massively produced througharc plasma for synthesizing carbon nanotube. Positive ions would have tendencies to move towards the negative charged cathode. The moving of the massive ions generated electric field in direction parallel with the ion movement. In this paper, we discuss the particle collisions subsequently resulting a new carbon species namely carbon nanotube (CNT) composed from single/many graphene layer rolled up alike nanostraw structure.